Perbedaan Hasil Belajar IPS Menggunakaan Model Pembelajaran Kooperatif Tipe NHT (numbered head together) Dengan Metode Konvensional Pada Siswa Kelas VIII SMP N 2 Bekasi - Vinsensius Mochamad Syah Rohman; Nadia Rista (Jurnal Web Informatika Teknologi, 2021)
This study aims to determine differences in social studies learning outcomes using NHT-type collaborative learning models (headed) in the traditional way of Class VIII SMP N 2 Bekasi. Increase a social studies learning outcomes tool was used in the form of learning outcomes tests to acquire the data. The study method used was an experimental design with a non-equivalent control group design (pre-test control group design), with 32 students from class VIII-A and 32 students from class VIII as experimental classes. I have a total sample. B as a control class. SMP N 2 Bekasi class. Obtained by intentional sampling. The results show that the learning outcomes of students treated with the NHT (numbered head together) collaborative learning model (mainly numbered) are significantly different from those of students using traditional methods. The results of the hypothesis test using SPSS version 20 of the group statistics table show that the average ability of the learning results using the NHT (numbered head together) type collaborative learning model (head number) is 82.06 and the standard deviation is 9,059. increase. Students' learning outcomes using traditional methods also mean 71.03 with a standard deviation of 8.712. This means that students using the NHT-type collaborative learning model (numbered at the beginning) have high learning outcomes. The results of this study are important for developing educational policies, especially those related to improving the quality of student learning outcomes.